Promoting Sustainable Marine Tourism Through Hospitality Management Study Programs: Hospitality Students' Perspectives on Marine Environmental Sustainability in Bali - Retny Asriyani; Ni Putu Lindawati; Bagus Putu Ekadharma Susila; I Wayan Agus Anggayana; Sulistyoadi Joko Saharajo; Eko Sulistyo (Politeknik Pariwisata Makassar, 2024)
This qualitative research examines the impact of the hospitality management study program on the promotion of sustainable marine tourism, with a focus on hospitality management students' views on marine environmental sustainability. Conducted at Triatma Mulya University, the study involved comprehensive interviews and focus groups with a diverse group of students, including first-year, third-year, and fifth-year students from the hospitality management study program. The aim is to understand how students perceive the integration of sustainability concepts into their education and how these perceptions influence their attitudes towards marine conservation. Through semi-structured interviews and group discussions, this research explores students' experiences with sustainability-oriented courses, their attitudes toward marine environmental protection, and their plans to apply these principles in their future careers. The study identifies key issues such as challenges students face in implementing sustainable practices, shortcomings in current educational approaches, and varying levels of commitment to marine environmental management. Students reported both enthusiasm for sustainability and difficulties in translating their learning into actionable practices, highlighting a gap between theoretical knowledge and practical application. The findings reveal that while students recognize the importance of sustainability, they encounter obstacles such as limited resources, insufficient practical experience, and a lack of support in applying sustainability concepts. This research underscores the need for enhancements in educational strategies, such as incorporating more hands-on experiences, case studies, and better alignment between academic content and industry practices. Insights from this study provide valuable information for educators and policymakers aiming to refine hospitality management programs to better promote sustainable marine tourism. By contributing to the broader discussion on incorporating sustainability into educational frameworks, this research emphasizes the critical need to prepare students with the skills, knowledge, and practical experience necessary to become effective advocates for marine environmental sustainability within the hospitality industry. This approach will help bridge the gap between education and real-world applications, fostering a more environmentally responsible workforce.